The intratumoral microbiome: Characterization methods and functional impact. (1st December 2021) - Heymann, Clément J.F.; Bard, Jean-Marie; Heymann, Marie-Françoise; Heymann, Dominique; Bobin-Dubigeon, Christine
Abstract: Live-pathogenic bacteria, which were identified inside tumors hundreds year ago, are key elements in modern cancer research. As they have a relatively accessible genome, they offer a multitude of metabolic engineering opportunities, useful in several clinical fields. Better understanding of the tumor microenvironment and its associated microbiome would help conceptualize new metabolically engineered species, triggering efficient therapeutic responses against cancer. Unfortunately, given the low microbial biomass nature of tumors, characterizing the tumor microbiome remains a challenge. Tumors have a high host versus bacterial DNA ratio, making it extremely complex to identify tumor-associated bacteria. Nevertheless, with the improvements in next-generation analytic tools, recent studies demonstrated the existence of intratumor bacteria inside defined tumors. It is now proven that each cancer subtype has a unique microbiome, characterized by bacterial communities with specific metabolic functions. This review provides a brief overview of the main approaches used to characterize the tumor microbiome, and of the recently proposed functions of intracellular bacteria identified in oncological entities. The therapeutic aspects of live-pathogenic microbes are also discussed, regarding the tumor microenvironment of each cancer type. Highlights: The tumor ecosystem is favorable for bacterial proliferation. The tumor microbiome is organ-specific. Live-pathogenic bacteria offer numerous possibilities for metabolic engineering. A better characterization of the roles played by tumor microbiote would help developing new personalized medicine.